Modulation of diverse oncogenic transcription factors by thymoquinone, an essential oil compound isolated from the seeds of Nigella sativa Linn - Shanmugam, M.; Arfuso, Frank; Kumar, Alan Prem; Wang, L.; Goh, B.; Ahn, K.; Bishayee, A.; Sethi, G. (Academic Press, 2017)
© 2017. Thymoquinone (TQ), isolated almost fifty years ago, is the main bioactive constituent of black seed essential oil extracted from the seed of Nigella sativa. TQ has been shown to have promising effects against a variety of inflammatory diseases and cancer. Cancer development is a multistep process where normal cells acquire qualities that enable the cells to proliferate continuously and migrate to distant sites in the human body. Drugs that interfere with this process are considered potential anti-cancer therapeutics, which may ultimately result in their clinical usage. TQ is once such compound which has been reported to modulate several major signaling pathways and key oncogenic molecules that play a prominent role in cancer initiation, progression, invasion, metastasis, and angiogenesis. Various studies have reported that TQ can enhance the anti-cancer potential when co-administered with several chemotherapeutic agents while reducing their toxic side effects. In addition, TQ has been shown to inhibit the growth of breast, prostate, pancreatic, colon, lung, and hematological malignancies in different mouse models of cancer. This review focuses on TQ's chemical and pharmacological properties, its diverse molecular targets and also provides clear evidence on its promising potential under preclinical and clinical settings.